Sodium restriction in patients with cirrhotic ascites: a protocol for a systematic review. Issue 1 (December 2016) - Walbaum, Benjamin; Valda, María; Rada, Gabriel
Abstract Background Avid renal sodium and water retention among other mechanisms produce ascites in patients with cirrhosis. The main guidelines recommend sodium intake reduction in order to counteract this complication. However, some randomized controlled trials have suggested a lack of benefit with a sodium-restricted over an unrestricted diet, and even an increase in ascites and renal complications has been reported. There are no systematic reviews addressing this question. Methods A systematic review protocol has been designed and will be reported in line with Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P). We will search for randomized controlled trials evaluating a salt-restricted versus unrestricted regime in patients with cirrhosis and ascites in EMBASE, MEDLINE, and the Cochrane Central Register of Controlled Trials. We will also try to identify literature by reviewing reference list of included studies and relevant reviews, screening main conference proceedings, and searching for unpublished and ongoing trials in the World Health Organization (WHO) International Clinical Trials Registry Platform. Two researchers will independently undertake selection of studies, data extraction, and assessment of the quality of included studies. We will estimate pooled risk ratios for dichotomous data and the mean difference or standardized mean difference for continuous outcomes. A random effect model will be used for meta-analyses. Data synthesis and other analyses will be conducted using RevMan software. Ethics and dissemination: no ethics approval is considered necessary. Results of this study will be disseminated via peer-reviewed publications and social networks Discussion Sodium restriction is a widely accepted coadjuvant therapy for ascites; however, this indication is based primarily on expert recommendations. As far as we know, this will be the first systematic review assessing the effects of a sodium-restricted diet for ascites in cirrhotic patients. Our systematic review will aim to provide a high-quality synthesis of current evidence for patients and clinicians about this question. The main limitation might result from the reduced number and quality of primary studies available. Systematic review registration: PROSPEROCRD42015022161